Implementation of Legal Aid Rights for Suspects Based on Justice Principles at Malang Police - Fatwa Azis Wicaksono; Setiawan Noerdajasakti; Bambang Sugiri (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
The right to legal aid is a constitutional right that must be granted to every suspect in the criminal justice process as a form of human rights protection and the realization of the principle of justice. The reform of criminal procedural law through Law Number 20 of 2025 concerning the Criminal Procedure Code strengthens the guarantee of legal assistance for suspects from the investigation stage. However, in practice, there are still various problems that affect the effectiveness of the implementation of these provisions. This study aims to analyze the effectiveness of the implementation of Article 155 paragraph (2) of Law Number 20 of 2025 in fulfilling the right to legal aid for suspects during the just investigation stage and to identify obstacles that affect its implementation. This study uses an empirical legal research method with a sociological juridical approach. The approaches used include a statute approach and a conceptual approach. Research data were obtained through interviews with law enforcement officers and related parties and supported by a literature study of relevant laws and regulations, books, journals, and literature. The research results show that the implementation of Article 155 paragraph (2) has provided a stronger legal basis in guaranteeing the right of suspects to obtain legal assistance during the investigation stage. This provision contributes to realizing the principles of fair trials, equality before the law, and protection of human rights. However, the effectiveness of its implementation still faces legal, structural, and legal culture obstacles that affect suspects' access to legal assistance. Therefore, it is necessary to strengthen implementing regulations, increase the capacity of law enforcement officers, optimize legal aid services, and increase public legal awareness in order to realize a criminal justice system that is fair, humanistic, and oriented towards the protection of human rights.